A focused issue on building new competences in dynamic environments - Heene, Aimé; Sanchez, Ron (Research in competence-based management, 2014)
Changing business environments challenge established management ideas and practices. This volume draws on competence-based theory to identify and elaborate some important ways in which organizational competences are evolving -- or should evolve -- to respond to some fundamental forms of change in business environments. Part I of the volume examines some key elements of emerging business models and strategies, including the impacts of cloud computing on international business models. Part II examines the kinds of new capabilities firms will need to develop to become competent in their new business models and strategies. Part III suggests how the challenges of rapidly evolving environments call for further development of competence-based management theory.